2015
DOI: 10.1080/19346182.2015.1064935
|View full text |Cite
|
Sign up to set email alerts
|

Detecting repetitions and time features in resistance training using triaxial accelerometry

Abstract: Accurately determining resistance-training parameters is crucial to gain knowledge about the training process and to evaluate training interventions. To current knowledge, no method exists to automatically detect a series of features in a repetition training session using one three-dimensional accelerometer. In this study, a specific algorithm was used to detect the number of repetitions and different time features. Features determined by the acceleration algorithm were compared to a reference system using a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Screening of the selected papers and the 23 reviews produced 77 additional papers. As a result, 286 studies were identified for inclusion in the systematic review [ 24 , 41 , 43 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , ...…”
Section: Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening of the selected papers and the 23 reviews produced 77 additional papers. As a result, 286 studies were identified for inclusion in the systematic review [ 24 , 41 , 43 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , ...…”
Section: Trendsmentioning
confidence: 99%
“…Both types of assessment have been performed using MIMUs that provide instantaneous acceleration (and therefore force) data along with an integrated measurement of velocity to determine muscular power: explosive performance was assessed for the lower limbs during jumps [ 13 , 83 , 84 , 92 , 93 , 97 , 100 , 117 , 150 , 166 , 167 , 199 , 213 , 218 , 219 , 220 , 233 , 244 , 251 , 257 , 258 , 281 , 286 ] and for the upper limbs [ 78 , 141 , 151 , 190 , 236 , 310 ]. Force and power production capacity were quantified during maximum dynamic strength tests for the upper limbs [ 76 , 97 , 103 , 172 , 186 , 198 , 252 , 261 , 305 ] and lower limbs [ 64 , 65 , 76 , 82 , 97 , 172 , 252 , 265 , 289 ]. As an indirect assessment of force production capacity, static muscular stiffness ha...…”
Section: Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of different cadences can affect the TUT and affect the training volume and intensity (15). The capacity to lift external load reduces from the increase of the TUT (1).…”
Section: Introductionmentioning
confidence: 99%